Analisis Ketidakselarasan Penggunaan Lahan Terhadap Rencana Detil Tata Ruang Kecamatan Kalasan Kabupaten Sleman Tahun 2015 - Bima, Dion Prabu Septa, Drs Musiyam M.Tp (2016)
The growth of urban areas in the district of Kalasan Sleman experiencing rapid growth. The growth of land use in the district of Kalasan must be controlled so that the land is used according to its spatial planning where to obtain the most out of the use of land based on land suitability. If not controlled then there will be a lot of use that is incompatible with the proper functioning it will appear a lot of problems within a period of five to ten years ahead. The main purpose of this study is to determine the distribution of unsuitability land use in Kalasan District and determine the most influential factor in unconformity. The method used is a qualitative method which will be grouped into three classes, unsuitable, suitable, and not suitable yet,. Then do the survey and interviews with respondents randomly scattered by the class to determine the main factors that cause unsuitability. Based on data processing and surveys conducted in Kalasan District of measuring 35.241.292 there are 112 182 (2.8%) is not suitable, composed of buildings constructed on agricultural land liberated, dry land farming, empty land, and the river banks, spread evenly throughout the region Kalasan District, and is also associated with the road. Based on the interview concluded that the main factors that most influence is economy and the necessities of life, and accessibility by road, as well as the level of risk of loss in agricultural processing.